2018
DOI: 10.3390/polym10111193
|View full text |Cite
|
Sign up to set email alerts
|

An RGD-Containing Peptide Derived from Wild Silkworm Silk Fibroin Promotes Cell Adhesion and Spreading

Abstract: Arginine-Glycine-Aspartate (RGD) tripeptide can promote cell adhesion when present in the amino acid of proteins such as fibronectin. In order to demonstrate the bioactivity of an RGD-containing silk protein, a gene encoding the RGD motif-containing peptide GSGAGGRGDGGYGSGSS (–RGD–) derived from nonmulberry silk was designed and cloned, then multimerised and inserted into a commercial pGEX expression vector for recombinant expression of (–RGD–)n peptides. Herein, we focus on two glutathione-S-transferase (GST)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Cell viability and cell adhesion studies were performed as per the published protocol, 15 but with slight modifications. The L929 mouse fibroblasts cells were obtained from NCCS‐Pune.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability and cell adhesion studies were performed as per the published protocol, 15 but with slight modifications. The L929 mouse fibroblasts cells were obtained from NCCS‐Pune.…”
Section: Methodsmentioning
confidence: 99%
“…The ECM proteins contain one or several short peptide motifs involved in several cellular processes such as cell adhesion, migration, and proliferation. The natural SF from various species of insects such as Antheraea yamamai and Antheraea pernyi has various RGD sites with the ability to improve cell adhesion, while the RGD content in the B. mori (silkworm) is lower [ 163 ]. Consequently, the integration of more informational molecules within the silkworm SF sequence is a strategy for increasing the performance of the silk fibroin.…”
Section: Increasing the Performance Of Silk Fibroin In Neural Tissmentioning
confidence: 99%
“…Consequently, the integration of more informational molecules within the silkworm SF sequence is a strategy for increasing the performance of the silk fibroin. Kang et al (2018) have produced recombinant SF films with RGD sequences integrated in the cloned gene of B. mori [ 163 ]. Furthermore, the peptide sequence IKVAV derived from laminin has shown a significant impact on the improvement of neurite growth and cell adhesion.…”
Section: Increasing the Performance Of Silk Fibroin In Neural Tissmentioning
confidence: 99%
“…Some wild silkworm species, which secrete a silk fibroin with higher cell affinity and adhesion due to the motif arginine-glycine-aspartate (RGD) in the protein chain, also result unsuitable for domestication, thus resulting in them being less indicated for biomaterial applications [ 29 ]. Silk represents a valuable biomaterial for various medical and pharmaceutical applications [ 30 ] and, beyond its well-known use as a suture material, the intense research and in vivo and in vitro studies on silk have revealed its huge potential for different clinical treatments [ 31 ], and for many biomedical applications due to its tunable properties and the possibility for it to be combined with other materials such as proteins, polymers and ceramics for improved properties and functions [ 30 , 31 ].…”
Section: Silk Fibroin As a Nature Derived Materials For Wound Healimentioning
confidence: 99%